1985
DOI: 10.1113/jphysiol.1985.sp015879
|View full text |Cite
|
Sign up to set email alerts
|

Responses of precentral cells during cooling of post‐central cortex in conscious monkeys.

Abstract: SUMMARY1. A cooling plate was implanted over the forelimb representation in area 2 of the post-central region of cerebral cortex in two monkeys.2. Recordings were made of the discharges of thirty-seven movement-related neurones (thirty-four precentral and three post-central) in the forelimb motor representation of the cerebral cortex during active and passively, imposed limb movements before, during and after cooling area 2 and local surrounding regions.3. Perfusion of the cooling plate with ice-cooled water f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…2,3 A study by using the technique of retrograde labeling with horseradish peroxidase in monkeys revealed that both precentral and postcentral gyri contained corticospinal cells. 36 Later, functional studies demonstrated that a lesion 37 or cooling, 38 confined to the presumed postcentral gyrus, resulted in hemiparesis of the contralateral upper extremity in monkeys. Neuroimaging studies by using fMRI revealed that motor tasks such as finger tapping or hand grasping consistently activated the contralateral postcentral gyrus defined by anatomic landmarks, in addition to the precentral, premotor, and supplementary motor areas.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 A study by using the technique of retrograde labeling with horseradish peroxidase in monkeys revealed that both precentral and postcentral gyri contained corticospinal cells. 36 Later, functional studies demonstrated that a lesion 37 or cooling, 38 confined to the presumed postcentral gyrus, resulted in hemiparesis of the contralateral upper extremity in monkeys. Neuroimaging studies by using fMRI revealed that motor tasks such as finger tapping or hand grasping consistently activated the contralateral postcentral gyrus defined by anatomic landmarks, in addition to the precentral, premotor, and supplementary motor areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that a lesion (Xerri et al, 1998) or cooling (Brinkman et al, 1985) confined to the presumed postcentral gyrus resulted in hemiparesis of the contralateral upper extremity in monkeys. A previous human study of epilepsy surgery in extratemporal lobe epilepsy suggested that surgical resection of the postcentral gyrus resulted in more pronounced deficits of the contralateral extremities compared to that after resection of the precentral gyrus (Polkey, 2000).…”
Section: Evidence From Lesion Studiesmentioning
confidence: 99%
“…This phenomenon is believed to be due to cortico-cortical connections between the primary and secondary sensory cortex and the primary motor cortex (19). The role of the primary sensory cortex in guiding motor movements has also been suggested in animal studies (19,32,33). Freezing the primary sensory cortex causes decreased speed and coordination of arm movements, and pharmacologic blockade results in decreased coordination of fine finger movements.…”
Section: Figurementioning
confidence: 99%